Field evaluation of the efficacy of the mosquito killing system - Wan-Norafikah O.; Azahari A. H.; Kamal-Hidayat K.; Salleh I.; Lee, H. L. (Penerbit Universiti Kebangsaan Malaysia, 2017)
A preliminary field study was undertaken to evaluate the efficacy of a mosquito trap; Mosquito Killing System (MKS) in capturing mosquitoes and other insects. MKS has an automatic activation by the use of a photocell. It is also supplemented with carbon dioxide and heat as attractants for mosquitoes and other insects. Three units of MKS were employed at three different locations within two study sites for ten days. The mosquitoes and other insects that were trapped in MKS were collected and morphologically identified daily in the laboratory. A total of 1,928 mosquitoes and other insects were trapped in all units of MKS. High numbers of mosquitoes (93.05%), particularly Aedes sp. and Culex sp. were captured from MKS. Among these, Culex quinquefasciatus (91.81%) was most abundant species collected. Only 0.84% of Aedes aegypti and Aedes albopictus trapped in MKS. Female mosquitoes (83.44%) were found to be more attracted to MKS compared to male mosquitoes of various species. These findings illustrated the potency of MKS utilization in surveillance and control activities of Cx. quinquefasciatus; a nuisance mosquito and also potential vector of urban brancroftian filariasis in Malaysia.